помогите решить: 4х(х-1)-(2х+5)(2х-5)=1;
3х-5(х+1)(х-1)+5(х+2)(х-2)=6;
3(2х+1)(2х-1)-4(3х-2)(3х+2) +6х(4х+1)=31 ?
Ответы
1)
4х(х-1)-(2х+5)(2х-5)=1
4х^2-4х-4х^2+10х-10х+25=1
-4х+25=1
4х=25-1
4х=24
х=24/4
х=6
Проверка:
4*6(6-1)-(2*6+5)(2*6-5)=1
24*5-(12+5)(12-5)=1
24*5-(12*12-12*5+5*12-5*5)=1
120-(144-60+60-25)=1
120-144+60-60+25=1
120+25-144=1
145-144=1
1=1
2)
3х-5(х+1)(х-1)+5(х+2)(х-2)=6
3х-5(х^2-х+х-1)+5(х^2-2х+2х-4)=6
3х-5(х^2-1)+5(х^2-4)=6
3х-5х^2+5+5х^2-20=6
3х=6+20-5
3х=21
х=7
Проверка:
3*7-5(7+1)(7-1)+5(7+2)(7-2)=6
21-5*(49-1)+5(49-4)=6
21-5*48+5*45=6
21-240+225=6
246-240=6
6=6
3)
3(2х+1)(2х-1)-4(3х-2)(3х+2) +6х(4х+1)=31
3(4х^2-1)-4(9х^2-4)+24х^2+6х=31
12х^2-3-36х^2+16+24х^2+6х=31
6х=31+3-16
6х=18
х=18/6
х=3
Проверка:
3(2*3+1)(2*3-1)-4(3*3-2)(3*3+2)+6*3(4*3+1)=31
3(6+1)(6-1)-4(9-2)(9+2)+18*13=31
3*35-4*77+234=31
105-308+234=31
31=31
1)(4х-4)х-(2х+5)(2х-5)-1=0
2)4х^2-4x-4x^2+25-1=0
3)-4x+24=0
4)24-4x=0
- 4x=-24
x=6
1)3х-5(х+1)(х-1)+5(х+2)(х-2)-6=0
2)3x-5x^2+5+5x^2-20-6=0
3)3x+5-20-6=0
4)3x-21=0
5)3x=21
x=7
1)12X^2-3-36x^2+16+6x(4x+1)-31=0
2)-24x^2-3+16+6x(4x+1)-31=0
3)-24x^2+13+6x(4x+1)-31=0
4)-24x^2+13+(24x+6)x-31=0
5)-24x^2+13+24x^2+6x-31=0
6)13-6x-31=0
7)-18+6x=0
8)x=186=3
9) x=3
^ в квадрате.